(untitled) (The Review of Diabetic Studies, 2024)
This comprehensive research article examines the multifaceted relationship between administrative workflow efficiency and patient satisfaction within healthcare facilities. It posits that beyond clinical competence, the quality and smoothness of the patient’s administrative journey—from initial contact to post-discharge follow-up—are critical determinants of overall experience and perceived care quality. The study employs a holistic, systems-based analysis, dissecting key administrative touchpoints: appointment scheduling and accessibility, streamlined check-in and registration, inter-departmental coordination and patient flow, and the discharge, billing, and follow-up processes. It further investigates the dual role of technology (EHRs, patient portals, digital tools) as both an enabler of efficiency and a potential source of new barriers, and underscores the indispensable human factor of staff training, communication, and the mitigation of administrative burden. The synthesis of these elements reveals that patient satisfaction is inextricably linked to the seamless integration of operational, technological, and human-centered strategies. The article concludes that intentional investment in end-to-end administrative workflow optimization is not merely an operational concern but a fundamental pillar of patient-centered care, directly impacting satisfaction scores, clinical outcomes, and institutional sustainability.